IN VIVO ANTI-PLASMODIAL AND IN VITRO ANTIOXIDANT ACTIVITY OF ETHANOLIC LEAF EXTRACT OF ALSTONIA BOONIE (EWE AHUN) AND ITS EFFECT ON SOME BIOCHEMICAL PARAMETERS IN SWISS ALBINO MICE INFECTED WITH PLASMODIUM BERGHEI NK 65 - Momoh J.; Longe A.O; Campbell C.A. (European Scientific Journal, ESJ, 2014)
Malaria is an increasing worldwide threat, with more than three hundred million infections and one million deaths every year.The study was conducted to determine the effect of in vivo anti-plasmodial and in vitro antioxidant activity of ethanolic leaf extract of Alstonia boonie (Ewe ahun) and its effect on some biochemical parameters in Swiss albino mice infected with Plasmodium berghei NK65. Swiss albino mice were inoculated intraperitoneally with Plasmodium berghei NK65. The mice were grouped into six groups, five per group. Group I were not infected with P.berghei, Group II and III served both as negative and positive controls respectively, while Group IV, V, and VI were treated with 200, 400, and 800 mg/kg body weight of A. boonie leaf extract respectively. The phytochemical constituents of the extract showed the presence of secondary metabolites like tannin, flavonoids, steroids and saponin. The extract caused 37.9%, 34.7% and 45.8% suppression in parasitaemia at 200, 400 and 800mg/kg body weight respectively while Chloroquine exerted 100% suppression at 5mg/kg body weight. The curative test shows that the different concentration of the extract exert a growth inhibition of 41.8%, 43.3% and 37.5% at 200, 400, 800mg/kg body weight respectively while Chloroquine, cleared the parasites by 93.1% at 5mg/kg body weight. The Hematological parameters showed that A. boonie had a significant increase (P<0.05) in HGB, RBC and HCT values while their WBC count reduced significantly when compared to the negative control. Chloroquine and the extract significantly decreases (P<0.05) plasma liver marker enzymes AST, ALT, ALP and GGT in the treated group compared to the untreated group. The total protein values significantly increased (P<0.05) in the group treated with the extract and at a dose of 800mg/kg, the extract was nephrotoxic. In the in-vitro antioxidant assay, the extract significantly increase (P<0.05) the level of CAT, SOD and GSH in the liver homogenate induced with oxidative stress using H2O2 while the MDA values reduced significantly with the administration of the extract.